PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT CENTRAL CAPITAL FUTURES CABANG MALANG - Isvandiari, Any; Idris, Bagus Al (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This study aims to determine: (1). The influence of leadership on employee performance of PT Central Capital Futures Malang Branch; (2). The influence of work discipline on employee performance of PT Central Capital Futures Malang Branch; (3). The influence of leadership and work discipline simultaneously on employee performance of PT Central Capital Futures Malang Branch. The research method is quantitative causality or causal with multiple linear regression analysis technique. The population is all 37 employees with 37 samples using full sampling (census). Hypothesis test using t test (partial) and F test (simultaneous). The result of t test (partial) shows that leadership has positive and significant effect to employee's performance, work discipline has positive and significant impact to employee's performance; and F test results (simultaneous) indicate that leadership And Work Discipline Together Effect On Employee performance.